Axonal Regeneration by Glycosaminoglycan - Sakamoto, Kazuma; Ozaki, Tomoya; Kadomatsu, Kenji (Frontiers in Cell and Developmental Biology, 2021)
Like other biomolecules including nucleic acid and protein, glycan plays pivotal roles in various cellular processes. For instance, it modulates protein folding and stability, organizes extracellular matrix and tissue elasticity, and regulates membrane trafficking. In addition, cell-surface glycans are often utilized as entry receptors for viruses, including COVID-19. Nevertheless, its roles as ligands to specific surface receptors have not been well understood. Recent reports have demonstrated that chondroitin sulfate and heparan sulfate, both of which are glycosaminoglycans, work as physiological ligands on their shared receptor, PTPσ. These two glycans differentially determine the fates of neuronal axons after injury in our central nervous system. That is, heparan sulfate promotes axonal regeneration while chondroitin sulfate inhibits it, inducing dystrophic endbulbs at the axon tips. In our recent study, we demonstrated that the CS-PTPσ　axis disrupted autophagy flux at the axon tips by dephosphorylating cortactin. In this review, we introduce how glycans work as physiological ligands and regulate their intracellular signaling, especially focusing on chondroitin sulfate.